Production and characterization of a biodegradable poly (hydroxybutyrate-co-hydroxyvalerate) (PHB-co-PHV) copolymer by moderately haloalkalitolerant Halomonas campisalis MCM B-1027 isolated from Lonar Lake, India - Kulkarni, S. O.; Kanekar, Pradnya P.; Nilegaonkar, S. S.; Sarnaik, S. S.; Jog, Jyoti Prakash (Bioresource Technology, 2010)
Several microorganisms produce polyhydroxyalkanoates (PHA). They are accumulated intracellularly as energy storage compounds. The PHAs are of interest because of their potential in biomedical applications. Halophilic bacteria and archaea are known to produce polyhydroxybutyrate (PHB). This paper describes production of a biodegradable copolymer, PHB-co-PHV by a moderately haloalkalitolerant Halomonas campisalis, isolated from Lonar Lake, India. The production of PHA was in the range of 45-81% on dry cell weight basis when the organism was grown in a production medium containing 1% (w/v) maltose and 0.1% (w/v) yeast extract, at pH ranging from 6 to 9 with an inoculum density of 10(5)-10(7) cells/ml of medium, for incubation period of 15-30 h and at 37 degrees C. The polymer produced by the organism is a hydroxyester with molecular weight of 1.3014 x 10(6). Its melting temperature was 171 degrees C. The (1)H NMR analysis revealed that the polymer was a copolymer of PHB-co-PHV. This could be achieved by providing simple carbon source viz. maltose. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable plastics; Halomonas campisalis; Polyhydroxyalkanoates

Characterisation of copolymer, poly (hydroxybutyrate-co-hydroxyvalerate) (PHB-co-PHV) produced by halomonas campisalis (MCM B-1027), its biodegradability and potential application - Kulkarni, Snehal O.; Kanekar, Pradnya P.; Jog, Jyoti Prakash; Patil, Prashant A.; Nilegaonkar, Smita S.; Sarnaik, Seema S.; Kshirsagar, Pranav R. (Bioresource Technology, 2011)
Characterisation of polyhydroxyalkanoate (PHA) film produced by haloalkalitolerant Halomonas campisalis (MCM B-1027) in 14 L SS fermenter revealed it to have composition of monomer units, HB:HV as 96:4 as analysed by (1)H NMR indicating the PHA as a co-polymer of PHB-co-PHV, molecular weight by gel permeation chromatography as 2.08 x 10(6), melting temperature 166.51 degrees C, tensile strength 18.8 MPa; two relaxations namely beta transition corresponding to the glass rubber transition and alpha transition corresponding to crystalline relaxation by Dynamic Mechanical Thermal analysis and only one relaxation corresponding to MWS interfacial polarisation with activation energy of 129 kJ/mol by broadband dielectric spectroscopy. Optical microscopic studies showed typical Maltese-cross pattern of spherulites. The PHA film was found to be biodegradable by standard ASTM method as well as by soil burial method. The leak proof polymer bags prepared from the film could be used as a packaging material. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymer; Copolymer PHB-co-PHV; Dielectric relaxation spectroscopy; Dynamic mechanical analysis; Halomonas

Purification and characterization of a thermolysin like protease from thermoactinomyces thalpophilus MCMB-380 - Majumder, Devipriya R.; Kanekar, Pradnya P.; Gaikwad, Sushama M. (Protein and Peptide Letters, 2013)
The extracellular thermolysin like protease (TLP) was purified and characterized from Thermoactinomyces thalpophilus MCMB-380 (Genbank Accession No. EF397000). The enzyme was purified to homogeneity by successive ultra filtration steps using 50 kDa and 10 kDa membrane filters followed by anion exchange chromatography. The molecular mass and isoelectric point of the enzyme were found to be 34.4 kDa and 9.5, respectively. The proteolytic activity was inhibited by EDTA and the enzyme required Ca2+ to show the full activity as well as thermostability. The T-50 of the enzyme at 80 degrees C was 1 h and the activation energy was estimated to be 11.02 Kcal / mol. Atomic absorption spectrophotometric analysis revealed the presence of Zn2+ ion in the protein core indicating that it is a metalloprotease. This protease has commercial potential in catalyzing the condensation reaction of two amino acids for production of the dipeptide aspartame, an artificial sweetener. The one hour time-frame is significantly faster than that of the enzyme thermolysin from Bacillus thermoproteolyticus. Moreover the TLP was stable at 80 degrees C for one hour which makes it industrially robust. The Zn2+ ion in the T. thalpophilus protease appears to be necessary for maintaining the active conformation of the enzyme molecule.
Keywords: Metalloprotease; Thermostability; TLP